Contributions of Individual, Family, and School Characteristics to Chilean Students’ Social Well-Being at School - López, Verónica; Torres-Vallejos, Javier; Ascorra, Paula; González, Luis; Ortiz, Sebastián; Bilbao, Marian (Frontiers in Psychology, 2021)
Schools are an essential part of students’ lives and can promote and facilitate their well-being. Although research on well-being among school-aged children and adolescents has distinguished subjective well-being from social well-being, very few studies examined student’s social well-being at school (SWS). SWS is understood as students’ valuation of the circumstances and functioning of their school. This framework posits that the context of the schools can shape students’ perception of feeling integrated and making significant contributions to their schools. However, not much is known regarding the joint contribution of individual, family, and school characteristics to students’ SWS. This study analyzed these joint contributions in a nationally representative sample of 6,389 children and adolescents enrolled in 5th–11th grades. Findings show that being female and younger were individual predictors of SWS. Students’ satisfaction with their family and fewer changes of schools were also significant contributors. When students’ perceptions of their schools were incorporated, the individual and family characteristics decreased or lost significance. In the full model, the highest contribution to SWS was explained by the school-level aggregated perception of school climate. These findings call for integrated policies and practices to foster students’ sense of belonging, feeling integrated, and contribution to their schools, with a focus on school-level interventions to improve SWS through positive and engaging school climates that foster students’ sense of agency.